2011
DOI: 10.1152/ajpcell.00321.2010
|View full text |Cite
|
Sign up to set email alerts
|

BTB-Kelch protein Krp1 regulates proliferation and differentiation of myoblasts

Abstract: The BTB-Kelch protein Krp1 is highly and specifically expressed in skeletal muscle, where it is proposed to have a role in myofibril formation. We observed significant upregulation of Krp1 in C2 cells early in myoblast differentiation, well before myofibrillogenesis. Krp1 has a role in cytoskeletal organization and cell motility; since myoblast migration and elongation/alignment are important events in early myogenesis, we hypothesized that Krp1 is involved with earlier regulation of differentiation. Krp1 prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 31 publications
2
21
1
Order By: Relevance
“…In proliferating C2C12 myoblasts SARCOSIN was already expressed at considerable levels, which is in contrast to results from Paxton et al, (2011) who observed absence of SARCOSIN (Krp1) expression in proliferating C2 cells. This could indicate that in our experiments some cells were already differentiating in the growth medium.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In proliferating C2C12 myoblasts SARCOSIN was already expressed at considerable levels, which is in contrast to results from Paxton et al, (2011) who observed absence of SARCOSIN (Krp1) expression in proliferating C2 cells. This could indicate that in our experiments some cells were already differentiating in the growth medium.…”
Section: Discussioncontrasting
confidence: 99%
“…A similar function for SARCOSIN in cultured cardiomyocytes has been reported (Greenberg et al, 2008). In differentiating C2C12 cells we observed SARCOSIN distributed rather evenly throughout the cytoplasm which indeed has been described very recently (Paxton et al, 2011), suggesting different functions for SARCOSIN in developing and adult muscle cells.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Immunofluorescence on cultured satellite cells and ex vivo muscle was performed as previously described [39,40].…”
Section: Immunofluorescence and Histologymentioning
confidence: 99%
“…Western blotting was performed as previously described [40], with the following antibodies (in addition to those above): p38 (Cell Signaling Technology), phospho-p38 (Cell Signaling Technology), p38a (R&D Systems, Abingdon, UK, http://www.rndsy stems.com), and GAPDH (Abcam, Cambridge, UK, http:// www.abcam.com).…”
Section: Western Blottingmentioning
confidence: 99%